The Correlation Between Health Locus of Control and Compliance In Taking Medication Toward Patients With Tuberculosis in the Working Area of Nosarara Public Health Center, Palu Central Sulawesi - Sulistiawati K. Lambeja; Ni Nyoman Udiani; Mutmaina (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Nosarara Public Health Center (PHC) is one of PHC that has the highest tuberculosis cases in Palu, and during 2023 had 81 cases, which about 34 (45%) patients who successfully recovered, 2 patients died, and 45 (55%) patients who were still on treatment. However, only 11 patients who underwent 6 months of the treatment process. The purpose of this study was to determine the correlation between Health locus of control with compliance in taking medication in Tuberculosis patients in the Nosarara Public Health Centre. Methods: This is a quantitative study with an analytical observational design with a cross-sectional approach. The total of population in this study were 81 TB patients who undergoing treatment at the Nosarara Public Health Centre, and the total of sample were 67 respondents that were taken by using the Slovin formula, and data analysis by using the Chi-square test. Results: This study shows that most respondents have a good Health Locus of Control (41.8%) and for treatment compliance category had non-compliant (62.7%), the results of the chi-square test of Health Locus of Control with compliance in taking medication = 0.000 <0.05 which indicates had a significant correlation. Conclusion: There is a correlation between health locus of control and medication compliance toward Tuberculosis patients in the Nosarara Public Health Centre working area. Suggestion: It is expected for patients to always cooperate and improve compliance so that Tuberculosis disease can be resolved properly.